2016
DOI: 10.1111/1753-0407.12424
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between dental caries and metabolic syndrome among 13 998 middle‐aged urban Chinese

Abstract: Dental caries were associated with MetS among middle-aged Chinese in the present study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 36 publications
3
34
1
6
Order By: Relevance
“…The reason why no association between periodontitis and MetS development was observed in this study may be that the prevalence of periodontitis among participants was lower than that in the Japanese national data by each age group (participants vs. Japanese national data: 27% vs. 43% in those 35-44 years old, 49% vs. 50% in those 45-54 years old, and 30% vs. 55% in those 55-64 years old). The present study's results were not consistent with these previous results [8,[13][14][15][16], possibly since the participants in the present study were relatively young. The prevalence of MetS, DMFT, missing teeth, and periodontitis tend to increase with age.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The reason why no association between periodontitis and MetS development was observed in this study may be that the prevalence of periodontitis among participants was lower than that in the Japanese national data by each age group (participants vs. Japanese national data: 27% vs. 43% in those 35-44 years old, 49% vs. 50% in those 45-54 years old, and 30% vs. 55% in those 55-64 years old). The present study's results were not consistent with these previous results [8,[13][14][15][16], possibly since the participants in the present study were relatively young. The prevalence of MetS, DMFT, missing teeth, and periodontitis tend to increase with age.…”
Section: Discussioncontrasting
confidence: 99%
“…2016. https://www.mhlw.go.jp/toukei/list/62-17b.html) were used as cut-offs. These results were consistent with a previous cross-sectional study [13], indicating that patients with two or more DMFT were more likely to develop MetS, although this association was not statistically significant. A meta-analysis investigating relationships between periodontitis and MetS indicated that individuals with periodontitis were more than twice as likely to develop MetS than those without periodontitis [8].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Além disso, a perda dos dentes pode prejudicar a adoção de práticas alimentares saudáveis, visto que aumenta o consumo de alimentos inadequados, menos consistentes e de alto valor calórico. Logo, podem propiciar o aumento da concentração de glicose na corrente sanguínea, comprometendo ainda mais a saúde desses indivíduos 36,37,38 . Ressalta-se que grandes perdas dentária observadas em diabéticos têm sido referidas na literatura 39,40 .…”
Section: Discussionunclassified